Estimated dietary sodium intake in Thailand: A nationwide population survey with 24‐hour urine collections. Issue 4 (8th January 2021) - Chailimpamontree, Worawon; Kantachuvesiri, Surasak; Aekplakorn, Wichai; Lappichetpaiboon, Raweewan; Sripaiboonkij Thokanit, Nintita; Vathesatogkit, Prin; Kunjang, Ananthaya; Boonyagarn, Natthida; Sukhonthachit, Penmat; Chuaykarn, Narinphop; Sonkhammee, Patthrapon; Khunsaard, Payong; et al.
Abstract: Thailand has committed to reducing population sodium intake by 30% by 2025. However, reliable nationally representative data are unavailable for monitoring progress toward the goal. We estimated dietary sodium consumption using 24‐hour urinary analyses in a nationally representative, cross‐sectional population‐based survey. We selected 2388 adults (aged ≥ 18 years) from the North, South, North‐east, Central Regions, and Bangkok, using multi‐stage cluster sampling. Mean sodium excretion was inflated by 10% to adjust for non‐urinary sources. Multivariate logistic regression was performed to assess factors associated with sodium consumption ≥ 2000 mg. Among 1599 (67%) who completed urine collection, mean age was 43 years, 53% were female, and 30% had hypertension. Mean dietary sodium intake (mg/day) was 3636 (±1722), highest in South (4108 ± 1677), and lowest in North‐east (3316 ± 1608). Higher sodium consumption was independently associated with younger age (Adjusted Odds Ratio (AOR) 2.81; 95% Confidence interval (CI): 1.53‐5.17; p = .001); higher education (AOR 1.79; 95% CI: 1.19‐2.67; p = .005), BMI ≥ 25 (AOR 1.55; 95% CI: 1.09‐2.21; p =.016), and hypertension (AOR 1.58; 95% CI: 1.02‐2.44; p = .038). Urine potassium excretion was 1221 mg/day with little variation across Regions. Estimated dietary sodium consumption in Thai adults is nearly twice as high as recommended levels. These data provide a benchmark for future monitoring.